Effects of Filled Nano-Al2O3 and Its Contents on Friction and Wear Properties of Hydrogenated Nitrile Butadiene Rubber - Xinyang Tan; Zenghui Liu (Advances in Polymer Technology)
A new hydrogenated nitrile butadiene rubber (HNBR) material filled with silane-modified nano-Al2O3 is developed in this work. Influence of the nano-Al2O3 and its contents on friction and wear performances of the HNBR materials is investigated. The nano-Al2O3 particles with different contents are added into the HNBR composites. Then, friction and wear tests are conducted using a pin-on-disk tribometer. Scanning electron microscope (SEM) is used to observe wear topography of the HNBR composite surfaces. Attenuated total reflection–Fourier transform infrared (ATR–FTIR) spectroscopy is used to investigate mechanism of nano-Al2O3 reinforcing HNBR. Results show that the filled nano-Al2O3 and its contents significantly affect friction and wear performances. Presence of the nano-Al2O3 obviously decreases friction coefficient and volume wear rate. Friction coefficient and volume wear rate of the composites reduce initially with the increase of nano-Al2O3 content and then increase with further increasing the nano-Al2O3 content. The HNBR material filled by the nano-Al2O3 with the content of 15 phr shows better antifriction and wear performances. SEM results indicate that the HNBR material filled by the nano-Al2O3 of 15 phr presents the best topography of wear surface compared with the HNBR materials filled by other nano-Al2O3 contents in this study. ATR–FTIR results show that mechanism of the nano-Al2O3 reinforcing HNBR for wear resistance is due to the graft reaction between the modified nano-Al2O3 and HNBR to form cross-linking networks around the Al2O3 nanoparticles, and self-polymerization of unsaturated groups on the surface of the nano-Al2O3 to form interpenetrating polymer networks with the HNBR molecular main chains.